위험 상황 대응을 위한 감각·지각 기반 안전 정보디자인 전략 - 김다솔(Dasol Kim); 류시천(Sicheon You) (스마트미디어저널, 2025)
As the need for design research to prevent social disasters and accidents emerges, information design strategies for responding to hazardous situations are becoming increasingly important. In this context, this study explores information presentation strategies that consider the sensory and perceptual stages from the perspective of safety information design. The study examines the concept and characteristics of safety information design, prioritizing stages of information processing, and explores human sensory and perceptual characteristics in hazardous situations, focusing on attention theory. Key findings include: 1) prioritizing the sensory and perceptual information processing stages, 2) the effectiveness of information delivery considering sensory and perceptual saliency, 3) the use of YES/NO contrasts, 4) the effectiveness of information presentation utilizing scene schematics, 5) the significance of self-referential narratives and storytelling, and 6) the prompt response induced by emotionally appealing information. This study suggests that a design approach considering attention capture at the sensory and perceptual stages in safety information design is crucial for enhancing safety levels. It is significant in that it proposes information presentation strategies that consider sensory and perceptual human characteristics manifested in hazardous situations. 사회적 재난과 사고를 예방하기 위한 디자인 연구의 필요성이 대두함에 따라 위험 상황을 대응하기 위한 정보디자인 전략이 더욱 중요해지고 있다. 이같은 맥락에서 본 연구는 안전 정보디자인 관점에서 감각과 지각 단계를 고려한 정보 제시 방안을 탐색했다. 연구는 안전 정보디자인의 개념과 특징, 정보처리 단계 우선순위를 고찰하고, 주의 이론을 중심으로 위험 상황에서 발현되는 감각과 지각 단계의 인적 특성을 탐색했다. 주요 발견점으로는 1) 감각과 지각 정보처리 단계의 우선적 고려, 2) 감각과 지각 현출성을 고려한 정보 전달의 효과성, 3) YES/NO 대조 활용, 4) 장면도식을 활용한 정보 표현의 효과, 5) 자기 참조적 내러티브와 스토리텔링의 유의성, 6) 감정 소구 정보의 신속한 반응 유도 효과 등이 있다. 이 연구는 안전 정보디자인에서 감각과 지각 단계의 주의포획을 고려한 디자인적 접근이 안전 수준 향상에 중요함을 시사하며, 위험 상황에서 발현되는 감각과 지각적 인적 특성을 고려한 정보 제시 방안을 제안했다는 점에서 의의가 있다.